The physician's Alzheimer's disease management guide: Early detection and diagnosis of cognitive impairment, Alzheimer's disease and related dementia - Allison B. Reiss; Donna de Levante Raphael; Nathaniel A. Chin; Vivek Sinha (AIMS Press, 2022)
Primary care professionals play a critical role in the care of their patients. In clinical practice, early detection and diagnosis of Mild Cognitive Impairment, Alzheimer's disease and related dementia are often missed or delayed. Disclosure of diagnosis is not timely or not revealed. Though the methods that could improve early detection and diagnosis have remained the same over the decades with little change, they provide opportunities for early intervention, treatment and improvement in patient care. Emerging research suggests that though the disease process begins years prior to the clinical diagnosis, the healthcare system and health care professionals remain distant and reluctant to provide the service of annual cognitive assessment, which has been recommended by the Medicare program for older adults aged 65 years and older. Findings support that Alzheimer's disease and related cognitive impairments have gone under detected, underdiagnosed and undertreated. This article seeks to provide valuable and equitable information in the form of a clinician's guide for removing the barriers to early detection and diagnosis of cognitive impairments and offers an unprecedented opportunity to improve the clinical outcomes and care of older adults with various levels of cognitive decline, including mild cognitive impairment, Alzheimer's disease, and related dementias. This article provides information on understanding and addressing the challenges faced by health care professionals, including primary care clinicians; removing the barriers to cognitive assessments; educating this professional group on the importance of brain health, early detection, and diagnosis for their older adult patients; and providing these professionals with the ability to transfer their knowledge into more defined care planning. Until cognitive screening has been fully accepted and implemented for the optimal the care of older adults, health-related efforts should include the promotion and education of brain health, early detection, and diagnosis in the education of health care providers.